Photoconductive zinc oxide-composite paper by pilot paper machine manufacturing. (13th December 2016) - Sandberg, Mats; Tordera, Daniel; Granberg, Hjalmar; Sawatdee, Anurak; Dedic, Dina; Berggren, Magnus; Jonsson, Magnus P
Abstract: Smart materials can be used for a wide variety of applications, including sensing and energy harvesting. Implementation of smart materials in large area devices requires scalable manufacturing. The use of paper-making techniques would offer an enormous production capacity, allowing for low-cost and large-scale manufacturing. In this work we present a successful pilot scale paper machine manufacturing of functional composite papers (100 m min −1 with a web width of 30 cm) based on cellulose fibres and commercial tetrapodal zinc oxide microwhiskers (ZnO-Ts). Carbon electrodes could successfully be printed on the paper to form complete electronic devices where the paper itself is the active material. This enabled development of a ZnO-composite paper photosensor, where we characterized its stability, sensitivity and speed. The devices show excellent photosensing properties over a wide range of light irradiances (0.01–1 Sun), including short response times (∼10 s) and long-term stability. Under simulated sunlight and a bias voltage of 1 V, small (0.5 cm 2 ) two-probe interdigitated photosensor devices provided 12 μ A photocurrent. Under the same conditions, four-probe measurements of the composite paper showed a sheet resistance of 6.9 · 10 7 Ω/sq. Four-probe measurements also demonstrated that the paper conductivity varies linearly with light irradiance. To the best of our knowledge, this is the first example of pilot paper machine production of an optoelectronic paper, demonstrating the potential for large-scale paper manufacturing of active smart paper from low-cost industrial bulk materials.